Impact of coffee exports on economic growth in Ethiopia; An empirical investigation - Netsanet Gizaw; Jemal Abafita; Tesfaye Melaku Merra (Cogent Economics & Finance, 2022)
The major objective of this study was to examine the impact of Coffee exports on economic growth in Ethiopia. The study employed an extended generalized Cobb-Douglas production function model using data from the National Bank of Ethiopia and World Bank data base from 1980 to 2017. All the variables were non stationary at level and integrated of order I (1), and then co-integration test was conducted to ensure the existence of long-run relationship using Johansen's approach. Consequently, all the variables confirmed co-integartion, and the conventional VECM was estimated to extract both short-run and long-run relationships, and finally, Granger causality test was conducted to diagnose the direction of causation. The finding of the study revealed that coffee exports have insignificant short-run impact on economic growth, but significant positive impact in long run. The result from causality exerted bidirectional relationship holds in Ethiopia's coffee exports, likewise the result from IRF revealed coffee exports has a positive impact on long-run economic growth. Besides, labor force, capital formation, non-coffee exports and real effective exchange rates included in the model were found positive and significant impact in long run. Furthermore, the coefficient of ECT is -0.4883 that shows any deviations from long-run equilibrium is corrected at 48.83% annually and converges towards its long-run equilibrium. Based on the findings, it is recommended that a long-run policy towards exports in general and coffee export in particular is believed to provide significant impact on economic growth. Thus, increasing efficiency of the sector and exporting coffee would enable Ethiopia to sustain domestic economic growth. Besides, values had better be added to coffee beans before exporting and when this is done, it will lead to a higher economic growth in long run.
Keywords: 330; Coffee; coffee exports; co-integration; conomic growth; exports; long run; Ethiopia